Electronic structure and d-band center control engineering over M-doped CoP (M = Ni, Mn, Fe) hollow polyhedron frames for boosting hydrogen production. (February 2019) - Pan, Yuan; Sun, Kaian; Lin, Yan; Cao, Xing; Cheng, Yuansheng; Liu, Shoujie; Zeng, Lingyou; Cheong, Weng-Chon; Zhao, Di; Wu, Konglin; Liu, Zhi; Liu, Yunqi; et al.
Abstract: The practical application of hydrogen evolution reaction (HER) through water splitting depends on the development of low cost and efficient non-noble-metal catalysts. As a potential electrocatalyst, the improvement of HER performance catalyzed by nanostructured transition metal phosphides still remains a great challenge. Tuning the novel nanostructure, morphology, and electronic state from nanoscale is of great important to achieve highly efficient HER electrocatalysts. Herein, we first developed an electronic structure and d -band center control engineering for accelerating the HER process in both acid and alkaline media over M-doped CoP (M = Ni, Mn, Fe) hollow polyhedron frames (HPFs), which were synthesized by a self-templating transformation (STT) strategy. Impressively, the HER electrocatalytic activity can be maximumly promoted and maintained at least 21 h for Ni-CoP/HPFs catalyst. Synchrotron-based X-ray absorption near-edge structure, X-ray photoelectron spectroscopy, auger electron spectroscopy, ultraviolet photoemission spectroscopy and density functional theory calculations consistently reveal the improved performance is attributed to the changes of the electronic structure and the downshift of d -band center after metal doping. The Ni-CoP/HPFs catalyst also indicates excellent activity with a cell voltage of 1.43 V to achieve the current density of 10 mA cm −2 and superior stability when it was employed as a cathode for HER and an anode for urea oxidation in 1 M KOH with 0.5 M urea. The success modulation of HER performance in current STT strategy will provide a promising pathway for designing various transition metal-doped compounds for energy-related catalysis processes. Graphical abstract: An electronic structure and d -band center control engineering was developed for accelerating the HER process over M-doped CoP (M = Ni, Mn, Fe) hollow polyhedron frames (HPFs) from a self-templating transformation strategy in atomic scale. The optimized Ni-CoP/HPFs catalyst can be used as a bifunctional catalyst for energy-efficient electrocatalytic hydrogen production due to the high urea oxidation performance. Highlights: An electronic structure and d-band center control engineering for accelerating the HER process was developed. The M-doped CoP hollow polyhedron frames were synthesized by a self-templating transformation strategy. The HER activity can be maximumly promoted and maintained for Ni-CoP/HPFs catalyst. The Ni-CoP/HPFs can be used as a bifunctional catalyst for energy-efficient hydrogen production. Reasonable mechanism for the improved catalytic activity was proposed.